Pengaruh Manajemen Sumber Daya Manusia Terhadap Keberlanjutan Bisnis Dalam Novel Sepatu Terakhir Karya Toni Tegar Sahidi - Diyah Ayu Febri Winarni; Lailatul Muniroh; Eva Dwi Kurniawan (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The novel The Last Shoe tells the story of the life of a father named Pak Marwan. The character Pak Marwan in the novel The Last Shoe is the main character of the story. Mr, Marwan is a shoe craftsman whose name is known as the “father of shoes”. Pak Marwan opened a shoe business and made the name of his village known to many people. This type of research is qualitative research which aims to understand social phenomena, including the phenomenon being studied. The descriptive method of analysis is to describe the facts followed by content analysis. The data in this research is in the form of discourse related to the object of research is the novel The Last Shoe by Toni Tegar Sahidi. The primary data source in this research is the next of the novel The Last Shoe. Data collection techniques use heuristic and hermeneutic reading methods. The results of this research are to find out the characterizations contained in the novel The Last Shoes by Toni Tegar Sahidi, namely responsible, hardworking, business style, and teaching employees to be independent.